2023
DOI: 10.21203/rs.3.rs-2510626/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Mangrove on Tidal Propagation in a Tropical Coastal Lagoon

Abstract: Very complex aquatic ecosystem, the mangrove forest colonizes coastal lagoons, estuaries and deltas in tropical and subtropical zones. This study investigates the impact of mangrove vegetation on tidal propagation in the Somone Coastal Lagoon, located on the Senegalese small coast. The analysis of new field data is complemented with the application of a 3D circulation model accounting for vegetation. The analysis of well-reproduced water levels and currents over the whole lagoon make it possible to spatially s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The accumulation of water upstream of the estuary could accelerate its salinisation. It has been verified in a tropical lagoon with a reverse estuary (Samou al., 2024). Thior et al (2019) demonstrated the reverse salinity character of the Casamance estuary, with salinity increasing from downstream to upstream is due to the absence of freshwater inflow during the dry period and also high evaporation of seawater flowing up the estuary.…”
Section: Relationships Between Distortion and Extreme Water Levelsmentioning
confidence: 76%
See 1 more Smart Citation
“…The accumulation of water upstream of the estuary could accelerate its salinisation. It has been verified in a tropical lagoon with a reverse estuary (Samou al., 2024). Thior et al (2019) demonstrated the reverse salinity character of the Casamance estuary, with salinity increasing from downstream to upstream is due to the absence of freshwater inflow during the dry period and also high evaporation of seawater flowing up the estuary.…”
Section: Relationships Between Distortion and Extreme Water Levelsmentioning
confidence: 76%
“…Recently, estuarine environments in Senegal have gained increasing scientific interest. The Somone lagoon is a notable example where the impact of mangroves on tidal wave propagation and hydro-sedimentary processes has been studied (Samou Seujip et al 2024;Sakho et al 2011Sakho et al , 2015. The study conducted by Brunet-Moret in 1970 examined the propagation of the tidal wave in the Casamance River up to 200 km from its mouth over two consecutive years.…”
Section: Introductionmentioning
confidence: 99%